Respiratory medication sales and urban air pollution in Brussels (2005 to 2011). (September 2016) - Casas, Lidia; Simons, Koen; Nawrot, Tim S.; Brasseur, Olivier; Declerck, Priscilla; Buyl, Ronald; Coomans, Danny; Nemery, Benoit; Van Nieuwenhuyse, An
Abstract: Background: We investigated the associations between daily sales of respiratory medication and air pollutants in the Brussels-Capital Region between 2005 and 2011. Methods: We used over-dispersed Poisson Generalized Linear Models to regress daily individual reimbursement data of prescribed asthma and COPD medication from the social security database against each subject's residential exposure to outdoor particulate matter (PM10 ) or NO2 estimated, by interpolation from monitoring stations. We calculated cumulative risk ratios (RR) and their 95% confidence intervals (CI) for interquartile ranges (IQR) of exposure for different windows of past exposure for the entire population and for seven age groups. Results: Median daily concentrations of PM10 and NO2 were 25 μg/m 3 (IQR = 17.1) and 38 μg/m 3 (IQR = 20.5), respectively. PM10 was associated with daily medication sales among individuals aged 13 to 64 y. For NO2, significant associations were observed among all age groups except > 84 y. The highest RR were observed for NO2, among adolescents, including three weeks lags (RR = 1.187 95%CI: 1.097–1.285). Conclusion: The associations found between temporal changes in exposure to air pollutants and daily sales of respiratory medication in Brussels indicate that urban air pollution contributes to asthma and COPD morbidity in the general population. Highlights: Air pollution is associated with increased sales of respiratory medications, even below European standards. The strongest associations are observed for NO2. Significant associations are observed from birth to young elderly ages.